Pengaruh Konsumsi Fast Food Terhadap Kejadian Obesitas Pada Tenaga Medis - Nurhidayah Tiasya Sanas; Zulfitrawati Zulfitrawati; Jeni Dianiati (Universitas Muhamadiyah Manado, 2022)
Increasing prosperity, technological advances and westernization can result in changes in lifestyle and eating patterns in society, especially medical personnel who are at the forefront of maintaining public health. However, ironically, they themselves are faced with a health risk that is no less serious, namely obesity. One of the factors that can influence obesity/overweight is the availability of cheap, fast but unhealthy food, one of which is fast food. Fast food consumption is increasing among medical personnel because this type of food tends to be easy to obtain, tastes delicious, and is served quickly. The nutritional content of food is no longer a consideration for medical personnel. The aim of this research is to determine the effect of fast food consumption on obesity in medical personnel. This type of research uses quantitative descriptive research methods with a cross sectional research design. The results of this study show that there is a direct influence of fast food consumption on the incidence of obesity (9.45%, T statistic 4.06%, α 5%). The conclusion is that excessive consumption of fast food can increase the risk of obesity in medical personnel. Efforts to prevent and control obesity need to be carried out comprehensively to maintain the health of medical personnel and improve the quality of health services.